Addressing privacy predicaments in the digital marketplace: A power‐relations perspective. (16th March 2020) - Bandara, Ruwan; Fernando, Mario; Akter, Shahriar
Abstract: The utilization and governance of the internet and adjacent disruptive technologies have created numerous challenges to ensuring consumer online privacy. This study employs the power–responsibility equilibrium theory to explore emerging online privacy issues in the data‐driven marketplace. This exploratory study, based on semi‐structured interviews, explains why online shopping consumers are increasingly worried about their privacy and why they behave in a manner that could be detrimental to the consumer–vendor relationship. The findings suggest that deficiencies of corporate privacy responsibility and regulatory protection have deprived consumers of privacy empowerment. These deficiencies have also accentuated perceived privacy contract violations to trigger privacy concerns and subsequent defensive responses. We identify enhancement of consumer privacy empowerment and assuagement of privacy contract violations as two separate mechanisms of addressing online privacy issues. We also highlight the importance of addressing power and responsibility dynamics for maintaining a healthy information‐exchange environment.